2016
DOI: 10.3892/ijo.2016.3663
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol inhibits migration of renal cell carcinoma through activation of RhoA/ROCK/MLC signaling pathway

Abstract: Abstract. Honokiol, a biologically active compound isolated from Magnolia bark, has been shown to possess promising anticancer effect through induction of apoptosis. However, there is a relative lack of information regarding its anti-metastatic activity. Renal cell carcinoma (RCC) is the most common malignancy of the adult kidney and is known for high risk of metastasis. Clinically, therapeutic methods for metastatic RCC cases are limited and efforts to exploit new treatments are still ongoing. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Honokiol has been described to regulate multiple signalling pathways, molecular and cellular targets including nuclear factor‐κB (NF‐κB), STAT3, epidermal growth factor receptor (EGFR), c‐Met, c‐FLIP, bone morphogenetic protein 7 (BMP7), p53, RhoA, cell survival signalling and cell cycle mediators . To identify the mechanisms involved in honokiol‐mediated growth inhibition of OSCC cells, three survival signalling including p38, Erk and JNK pathways and four autophagy‐related signalling pathways including AMPK, Akt/mTOR, BNIP3 and Beclin‐1 were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honokiol has been described to regulate multiple signalling pathways, molecular and cellular targets including nuclear factor‐κB (NF‐κB), STAT3, epidermal growth factor receptor (EGFR), c‐Met, c‐FLIP, bone morphogenetic protein 7 (BMP7), p53, RhoA, cell survival signalling and cell cycle mediators . To identify the mechanisms involved in honokiol‐mediated growth inhibition of OSCC cells, three survival signalling including p38, Erk and JNK pathways and four autophagy‐related signalling pathways including AMPK, Akt/mTOR, BNIP3 and Beclin‐1 were examined.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH was used as an internal control. signalling and cell cycle mediators [11,[49][50][51][52]. To identify the mechanisms involved in honokiol-mediated growth inhibition of OSCC cells, three survival signalling including p38, Erk and JNK pathways and four autophagy-related signalling pathways including AMPK, Akt/ mTOR, BNIP3 and Beclin-1 were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the important steps in cancer management is to control tumour cell metastasis, especially for early-stage cancer patients [153]. Various studies have reported that honokiol has the capability to suppress tumour metastasis in different types of cancer including breast cancer [40,148,154], non-small cell lung cancer [44,155] ovarian carcinoma cells [28], lung cancer [50], U251 human glioma, as well as U-87MG and T98G human glioblastoma cell [63,65,94], oral squamous cell carcinoma (OSCC) [26], bladder cancer cell [143], pancreatic cancer [58], renal cell carcinoma [156,157], and gastric cancer cells [113]. For instance, the percentage of invading urinary bladder cancer (UBC) cells was significantly reduced by 67% and 92% upon 2.4 µg/mL and 4.8 µg/mL of honokiol treatment, respectively [143].…”
Section: Suppression Of Migration Invasion and Angiogenesis Of Cancementioning
confidence: 99%
“…Our study indicated that honokiol administration could downregulate BCL2 expression, promote the caspase‐3 signaling pathway, and accelerate cell apoptosis. Cell migration is an important process in tumor metastasis and progression . Several studies have reported that honokiol can inhibit the migration of various kinds of malignancies under different mechanisms .…”
Section: Discussionmentioning
confidence: 99%